The Requirements of Managing Phase I Clinical Trials Risks: The British and Italian Case Studies - Davide Di Tonno; Laura Martena; Manuela Taurisano; Caterina Perlin; Anna Chiara Loiacono; Stefano Lagravinese; Santo Marsigliante; Michele Maffia; Susanna Esposito; Gianluca Villa; Giovanni Gori; Leonardo Bray; et al. (MDPI AG, 2024)
Phase I clinical trials represent a critical point in drug development because the investigational medicinal product is being tested in humans for the first time. For this reason, it is essential to evaluate and identify the Maximum Tolerated Dose (MTD) and the safety of the new compound. To mitigate the possible risks associated with drug administration and treatment, the European Competent Authority issued various guidelines to provide provisions and harmonize risk management processes. In the UK and Italy, particular attention should be paid to the Medicines & Healthcare Products Regulatory Agency (MHRA) phase I accreditation scheme and the specific rules set by the Italian Drug Authority through the AIFA Determination no. 809/2015. Both reference documents are based on the concept of quality risk management while conducting phase I clinical studies. Moreover, the AIFA determination outlines specific requirements for those sites that want to conduct non-profit phase I clinical trials. Indeed, the document reports peculiar activities to the "Clinical Trial Quality Team", which is a team that should support the clinical site researchers in designing, starting, performing, and closing non-profit phase I studies. In this paper, we provide a general overview of the main European guidelines concerning the management of risks during phase I trials, focusing on the main peculiarities of the schemes and rules set by the MHRA and AIFA.